Assessing the impact of heat stress exposure on heat strain: An analysis of outdoor and semi-outdoor roof tile workers using the Physiological Strain Index - Putri, Nasya Adelia; Denny, Hanifa Maher; Rahfiludin, Mohammad Zen; Lestantyo, Daru (International Journal of Occupational Safety and Health, 2026)
Introduction: This study evaluates the prevalence and contributing factors of heat strain among roof tile workers exposed to temperatures exceeding occupational limits. Furthermore, it assesses how these heat-related health risks vary between male and female workers in semi-outdoor environments.Methods: This cross-sectional study involved 107 roof tile workers in Grobogan, Indonesia, utilizing validated questionnaires, WBGT measurements, and the Physiological Strain Index (PSI) to evaluate heat strain. Data were analyzed using Spearman’s rank, Pearson correlation, and chi-square tests to identify significant relationships between individual, occupational, and behavioral factors.Results: The PSI results of roof tile makers had an average score of 5.05 ± 0.40. The results demonstrated that female workers exhibited significantly higher physiological strain than males, primarily driven by biological differences in thermoregulatory capacity and greater adipose tissue insulation (p=0,000). Factors associated with heat strain were age (p=0.004), BMI (p=0.023), daily water intake (p=0.014), rest hours (p=0.000), heat stress (p=0.016), and workload (p=0.000).Conclusion: Despite natural acclimatization keeping overall strain moderate, heat stress, physical workload, female gender, and poor hydration remain critical determinants of physiological heat strain.